Readers' Regulation and Resolution of a Scientific Conflict Based on Differences in Source Information: An Eye-Tracking Study. Issue 5 (3rd July 2021) - Gottschling, Steffen; Kammerer, Yvonne
ABSTRACT: This eye-tracking study examines how differences in sources' trustworthiness are used by readers to regulate and resolve conflicting scientific claims. One hundred forty-four university students were sequentially presented with two conflicting scientific claims (regarding nanotechnology) across two texts. The claims were indicated to stem from two high-trustworthiness sources, two low-trustworthiness sources, or one high-trustworthiness source and one low-trustworthiness source. After having read the claims, participants rated their subjective explanations for the conflict, their personal claim agreement, and behavioral intent and completed a source-memory task. In line with our predictions, trustworthiness differences resulted in increased visual attention to source information as compared to when both sources were of equal trustworthiness. Trustworthiness differences also affected subjective conflict explanations, claim agreement, and behavioral intent. We discuss these results in the context of the Content-Source Integration model and propose an additional differentiation between readers' consideration of source information for conflict regulation and conflict resolution.